2020
DOI: 10.3390/jpm10040258
|View full text |Cite
|
Sign up to set email alerts
|

Of rAAV and Men: From Genetic Neuromuscular Disorder Efficacy and Toxicity Preclinical Studies to Clinical Trials and Back

Abstract: Neuromuscular disorders are a large group of rare pathologies characterised by skeletal muscle atrophy and weakness, with the common involvement of respiratory and/or cardiac muscles. These diseases lead to life-long motor deficiencies and specific organ failures, and are, in their worst-case scenarios, life threatening. Amongst other causes, they can be genetically inherited through mutations in more than 500 different genes. In the last 20 years, specific pharmacological treatments have been approved for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 289 publications
(241 reference statements)
0
18
0
2
Order By: Relevance
“…Thus, special attention should be given when treating patients with preexisting hepatic conditions, which is common for IMLD patients. 142 However, it is noteworthy to indicate that clinical trials using AAV for AIP, OTC deficiency, or GSD1a have not reported major adverse events. 85 An additional very important immune-related limitation is the presence of preexisting humoral antibodies and memory T cells against the viral vectors which can completely block liver transduction.…”
Section: Retroviral and Lentiviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, special attention should be given when treating patients with preexisting hepatic conditions, which is common for IMLD patients. 142 However, it is noteworthy to indicate that clinical trials using AAV for AIP, OTC deficiency, or GSD1a have not reported major adverse events. 85 An additional very important immune-related limitation is the presence of preexisting humoral antibodies and memory T cells against the viral vectors which can completely block liver transduction.…”
Section: Retroviral and Lentiviral Vectorsmentioning
confidence: 99%
“…Thus, special attention should be given when treating patients with pre-existing hepatic conditions, which is common for patients with IMLD. 142 However, it is noteworthy that clinical trials using AAV for AIP, OTC deficiency, or GSD1a have not reported major adverse events. 85 …”
Section: Relevant Aspects To Consider Current Limitations and Possible Future Directions In Liver-targeted Gene Therapymentioning
confidence: 99%
“…Une amélioration du transgène est également visée. Il semble que les micro-dystrophines comportant des domaines de type spectrine R16-R17 (domaines impliqués dans la liaison avec le régulateur du métabolisme cellulaire via l'oxyde nitrique synthase), pourraient avoir des avantages thérapeutiques supplémentaires [10].…”
Section: Modèles Animauxunclassified
“…The continuing development and application of multiomics methods offer particular challenges and opportunities, not least in the potential for personalized medicine. More than 500 different genes are known to be associated with neuromuscular disorders [1], and the identification of causative mutations has allowed the development of personalized therapies [1,2]. However, even if great progress has been made during the last two decades in different subgroups of neuromuscular disorders, there are still numerous challenges to resolve, such as the optimization of therapeutic knock-down strategies [3], targeting specific muscles and/or tissues of the nervous system [1], identifying genetic modifiers that can impair a therapeutic strategy [2], targeting common pathways being affected in different patient subgroups for a given disease [4,5], or understanding the impact of neuromuscular disorders on other tissues that could be affected but may be understudied.…”
mentioning
confidence: 99%
“…More than 500 different genes are known to be associated with neuromuscular disorders [1], and the identification of causative mutations has allowed the development of personalized therapies [1,2]. However, even if great progress has been made during the last two decades in different subgroups of neuromuscular disorders, there are still numerous challenges to resolve, such as the optimization of therapeutic knock-down strategies [3], targeting specific muscles and/or tissues of the nervous system [1], identifying genetic modifiers that can impair a therapeutic strategy [2], targeting common pathways being affected in different patient subgroups for a given disease [4,5], or understanding the impact of neuromuscular disorders on other tissues that could be affected but may be understudied. This Special Issue, entitled "Understanding Neuromuscular Health and Disease: Advances in Genetics, Omics, and Molecular Function", encompasses some 15 publications from colleagues working on a diverse range of neuromuscular diseases, including Duchenne muscular dystrophy [6][7][8][9], facioscapulohumeral dystrophy [3,10,11], amyotrophic lateral sclerosis [4,5,12], spinal muscular atrophy [2], Emery-Dreifuss muscular dystrophy [13], and rheumatoid arthritis [14].…”
mentioning
confidence: 99%